Insecurity: A Major Challenge against the Achievement of Sustainable Development Goals in Nigeria - Hamidu, Ishaku (Kashere Journal of Politics and International Relations, 2024)
Sustainable Development Goals (SDGs) as an international socioeconomic programme, was initiated by the United Nations to meet the yearnings and boost the livelihood of the global population domiciled in various countries by the year 2030. Nigeria, like other countries across the globe have domesticated the 17 SDGs and put machinery in place to that effect. Paradoxically however, this study disclose that there are traditional factors and various forms of insecurity serving as major impediments against sustaining the SDGs, with lots of implications on the country. The study recommends that authorities are to awake and ensure that lasting security is provided in the country. This will provide the enabling environment for food production, overcoming hunger/starvation and making educational system to flourish and the citizens will be mentally and socially healthy as envisioned in the SDGs programme.